Waste Management in Heritage Tourism Area: Perspectives from Visitors and Waste Management Operators - Faruq Al Muqsit; Rukuh Setiadi; Alex Lo (Pusbindiklatren Bappenas, 2024)
Waste management is a complex challenge for cities in developing countries, including Indonesia. This issue is particularly severe in heritage tourism areas, where unmanaged waste can affect the aesthetics and image of historic places. Therefore, this study aimed to investigate the sustainability aspects of waste management using heritage visitors’ destinations and waste management operator areas of the Old City of Semarang. A quantitative method was used to achieve this objective, and data were collected through questionnaires, interviews, field observations, document reviews and analyzed using descriptive methods. The results showed that visitors had positive behavior and awareness regarding waste management. Furthermore, sustainable waste management was implemented but not fully realized across all aspects. This study offered various measures to improve sustainable waste management in area, including waste sorting, collaboration between stakeholders, and policy advocacy on sustainable waste management.